Respostas
respondido por:
16
-x+2y=12 e 3x+8y=31
-x=12-2y *(-1) => x=2y-12
3x+8y=31 => 3*(2y-12)+8y=31 => 6y-36+8y=31 => 14y=31+36 =. 14y=67 => y=67/14 => y≈4,8
x=2y-12 => x=2*4,8-12 => x=9,6-12 => x≈-2,4
não, o par (-3,5) não resolvem o sistema
-x=12-2y *(-1) => x=2y-12
3x+8y=31 => 3*(2y-12)+8y=31 => 6y-36+8y=31 => 14y=31+36 =. 14y=67 => y=67/14 => y≈4,8
x=2y-12 => x=2*4,8-12 => x=9,6-12 => x≈-2,4
não, o par (-3,5) não resolvem o sistema
Perguntas similares
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás